Controllable poly-crystalline bilayered and multilayered graphene film growth by reciprocal chemical vapor deposition1. Issue 23 (21st June 2015) - Wu, Qinke; Jung, Seong Jun; Jang, Sung Kyu; Lee, Joohyun; Jeon, Insu; Suh, Hwansoo; Kim, Yong Ho; Lee, Young Hee; Lee, Sungjoo; Song, Young Jae
<x xml:space="preserve">Abstract</x> We report the selective growth of multi-layer graphene or a bilayer graphene film by reciprocal chemical vapor deposition.